2019
DOI: 10.2147/ndt.s227386
|View full text |Cite
|
Sign up to set email alerts
|

<p>Reversible Affective Symptoms and Attention Executive Control Network Impairment Following Thyroid Function Normalization in Hyperthyroidism</p>

Abstract: Introduction: Affective symptoms and attention impairments are found in patients with hyperthyroidism. Our previous data have revealed that the patients with hyperthyroidism experience impairments of the attention networks, but it remains unclear whether these disorders persist after the treatment of hyperthyroidism. Methods: Twenty healthy controls and 25 hyperthyroid patients were recruited and performed the attention network test (ANT) which can simultaneously examine the alertness, orientation and executio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…This time interval might be too short for any difference to be detected, because it has been reported that some patients who achieve euthyroid function after treatment might still have neuropsychological problems. 8 , 23 However, in terms of the quality of informed consent it is important that patients’ decisions would not fluctuate over such a short period. Our results suggest that as long as their mental status is not seriously impaired, informed consent obtained from patients with Graves’ thyrotoxicosis is robust and independent of thyroid function state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This time interval might be too short for any difference to be detected, because it has been reported that some patients who achieve euthyroid function after treatment might still have neuropsychological problems. 8 , 23 However, in terms of the quality of informed consent it is important that patients’ decisions would not fluctuate over such a short period. Our results suggest that as long as their mental status is not seriously impaired, informed consent obtained from patients with Graves’ thyrotoxicosis is robust and independent of thyroid function state.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] These mental symptoms usually disappear after reaching euthyroidism. 7,8 Although the biological mechanism for these symptoms remains unknown, recent studies using functional neuroimaging techniques of positron emission tomography (PET) and single photon emission computed tomography (SPECT) have revealed that excessive thyroid hormone induces abnormal metabolism in the limbic system and frontal cortex. [9][10][11] Informed consent for clinical treatment has evolved to become vitally important in modern medical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The mainstay of treatment in patients with psychomotor retardation, psychiatric features, and hyperthyroidism is the restoration of euthyroid status. Nurse practitioners should reassure the patient and family that the symptoms of confusion, depression, psychomotor retardation, fatigue, and unintentional weight loss should improve and be resolved in a few weeks (Yuan et al, 2019). Additionally, clinicians should encourage adequate hydration, food intake, and the implementation of safety protocol to decrease negative outcomes (Kennedy-Malone, 2020).…”
Section: Managementmentioning
confidence: 99%
“…In GD patients with a previous ability to manage a full-time job, one-third were unable to resume the same work ability after treatment ( 6 , 7 , 8 , 9 , 10 , 11 ). The cognitive problems reported, primarily memory and concentration deficits, are seldom captured with standard neuropsychological tests ( 10 , 12 ), while more demanding tests have shown altered decision-making and attention when suffering from hyperthyroidism compared to controls ( 13 , 14 ). There are contradictory results regarding cognitive tests at follow-up ( 1 , 14 ).…”
Section: Introductionmentioning
confidence: 98%